Transformasi Mitos Cadu ka Haji: Antara Tradisi Lokal dan Ajaran Islam di Masyarakat Cipaku, Sumedang - Maulana, Ilman; Hernawan, Wawan; Halim, Ilim Abdul (Balai Diklat Keagamaan Bandung, 2025)
This study aims to describe the continuity and role of this myth in the religious life of the local community, as well as to understand how this myth intertwines with the Islamic teachings they adhere to. This study uses an anthropological approach and qualitative research through literature review, participant observation, and in-depth interviews with community leaders. The analysis is conducted using Claude Lévi-Strauss's structuralism theory, which views myth as a cultural mechanism for managing the fundamental contradictions of human life. The results show that the myth of